Problems of Legal Efforts to Resist Execution in District Courts and High Courts up to Cassation and Judicial Review - Ahmad Haikal; Evita Isretno Israhadi (Yayasan Adra Karima Hubbi, 2024)
Background. The execution challenge process in Indonesia faces numerous obstacles, including procedural ambiguity, administrative inefficiencies, and case backlogs. These challenges lead to prolonged case resolution and undermine public trust in the legal system, especially among individuals with limited legal knowledge or financial resources. Purpose. This study aims to identify the main obstacles in the execution challenge process and assess their impact on legal certainty and access to justice. It also seeks to propose solutions to enhance the effectiveness and fairness of the legal system. Method. A qualitative approach was used, involving case studies, interviews with legal practitioners, and a review of legal documents to analyze procedural gaps and their effects on stakeholders. Findings. The study found that procedural complexity and administrative delays are significant obstacles, causing legal uncertainty and harming public trust. Furthermore, limited access to legal aid for disadvantaged individuals exacerbates inequality in the justice system. Conclusion. Simplifying procedures, incorporating technology in court administration, and enhancing public legal education are essential reforms to improve efficiency and accessibility. These measures will promote legal certainty and ensure equal justice for all.